Influence of endophytic fungal elicitation on production of inophyllum in suspension cultures of Calophyllum inophyllum L. - Pawar, Kiran D.; Yadav, Amit V.; Shouche, Yogesh S.; Thengane, Shubhada Ratnakar (Plant Cell Tissue and Organ Culture, 2011)
The influence of dried cell powder and culture filtrates of endophytic fungi on production of inophyllum in cell suspension cultures of leaf- and stem-derived callus of Calophyllum inophyllum was investigated. Two fungi, Nigrospora sphaerica and Phoma spp., endophytic to C. inophyllum, were isolated from leaf tissues, and were identified by both 18S rRNA gene amplification and sequencing. Elicitation of suspension cultures of both callus types of C. inophyllum with dried cell powder and culture filtrates of both fungi consistently elicited production of inophyllum A, B, C, and P. In comparison to stem-derived callus, suspension cultures of leaf-derived callus enhanced production of most inophyllum. Of the four inophyllum studied, the highest production of inophyllum A, C, and P was achieved in elicited suspension cultures of leaf-derived callus. Suspension cultures of stem-derived callus enhanced production only of inophyllum B. When suspension cultures of leaf-derived callus were elicited with 40 mg dried cell powder of Phoma spp., a level of 751-fold (6.84 mg/100 g elicited biomass) of inophyllum A was produced, compared to control. Whereas, a level of 414-fold (6.22 mg/100 g elicited biomass) of inophyllum B was produced when suspension cultures of stem-derived callus were elicited with 20 mg dried cell powder of N. sphaerica. When compared to control, a 10% culture filtrate of N. sphaerica in suspension cultures of leaf-derived callus elicited inophyllum C and P production by 928-fold (7.43 mg/100 g elicited biomass) and 750-fold (1.5 mg/100 g elicited biomass), respectively.
Keywords: Biotic elicitation; Calophyllum inophyllum; Endophytic fungi; Inophyllum; Suspension cultures